The Kopernikus ENSURE Co-Demonstration Platform - Mehlmann, Gert; Kuhnapfel, Uwe; Wwege, Felix; Winkens, Alexander; Scheibe, Christian; Vogel, Steffen; Noglik, Peter; Gratza, Michael; Richter, Julian; Weber, Moritz; Burlakin, Ilya; Kuri, Ananya; et al. (IEEE Open Journal of Power Electronics, 2023)
The Kopernikus ENSURE Co-Demonstration Platform enables the investigation of components and processes for the changing power system with grid models adapted to the respective problem. The platform is developed from the power system's perspective. A central aspect of the platform is to analyze several technical solutions of different stakeholders in shared power system models. Furthermore the platform enables the investigation of interactions between different technologies, the system stability or protection scenarios that cannot be simulated in the real power system or only to a very limited extent. The comparison of solution approaches on a common model basis enables reliable overall systemic statements. To realize this, a multi-domain and multi-vendor approach is pursued, covering electromagnetic transients, electromechanical transients, continuous power flow simulations, and real-time simulators from different manufacturers. The core components of the platform are distributed real-time simulations, including the coupling of different laboratories in Germany and the developed power system models. Investigations with the real-time capable platform can be carried out purely simulatively or, depending on the connected laboratory, as Control/Power-Hardware-in-the-Loop simulations.
Created from Fastlane, Scopus look-up
Keywords: Digital images; Digital twins; Distributed Co-Simulation; Electromagnetic Transients; Electromechanical Transients; Hardware-in-the-Loop; HVDC transmission; Load modeling; Power system dynamics; Power system stability; Power System Stability; Real-time systems